Anticoccidial Activity of Qinghao Powder Against Eimeria tenella in Broiler Chickens - Wang, Ling; Guo, Wenzhu; Haq, Shahbaz Ul; Guo, Zhiting; Cui, Dongan; Yang, Feng; Cheng, Feng; Wei, Xiaojuan; Lv, Jiawen (Frontiers in Veterinary Science, 2021)
High-performance liquid chromatography (HPLC) and thin-layer chromatography (TLC) were used to detect artemisinin in Qinghao Powder (QHP) for quality control. The level of artemisinin in QHP was 81.03 mg/g. A total of 210 chicks (14 days of age) were divided randomly into seven groups: three QHP treatments (0.15, 0.30, and 0.60 g/kg), a toltrazuril control (1.00 mL/L), a sulfachloropyrazine sodium control (SSC, 0.30 g/L), an E. tenella-infected control, and a healthy control group. All the groups were inoculated orally with 7 × 104 E. tenella oocysts except for the healthy control group. After seven days of administration, compared with the infected control group, chicks which were administered QHP, SS, and toltrazuril showed less bloody feces, oocyst output, and cecal lesions, and the protection rates were improved. The maximum rBWG and ACI were found in the SS-medicated group, followed by the groups medicated with 0.60 and 0.30 g/kg QHP. Therefore, a 0.30 g/kg dose level of QHP in the feed was selected as the recommend dose (RD) in the target animal safety test, in which 80 broiler chicks (14 days of age) were randomly divided into four major groups (I-healthy control group; II-1× RD; III-3× RD; IV- 6× RD), with each group subdivided into two subgroups (A and B) consisting of 10 chicks each. After 7-day (for sub-group A) or 14-day (for sub-group B) administration, compared with the healthy control, treatment-related changes in BWG, feed conversion ratio (FCR), relative organ weight (ROW) of the liver, WBC counts, and levels of RBC, HGB, ALT, AST, and TBIL were detected in the 3× and 6× RD groups. No differences were noted in necropsy for all doses, and histopathological examinations exhibited no QHP-associated signs of toxicity or abnormalities in the liver or kidney. The findings suggest that QHP at a dose of 0.30 g/kg feed would be appropriate for thetherapy and intermittent treatment of E. tenella-infected chicks, the dosage in clinical applications should be set according to the recommended dose to ensure animal safety.